2009
DOI: 10.1063/1.3186756
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform microwave spectra of a “new” isomer of OCS-CO2

Abstract: The rotational spectrum of a "new" isomer of OCS-CO(2) has been measured between 5 and 18 GHz using Fourier transform microwave spectroscopy. Both a- and b-type transitions of the parent dimer and the (13)CO(2)-containing isotopologue were fit and the resulting spectroscopic constants confirm that this is the planar O-interior, not-quite-as-parallel isomer that was experimentally observed for the first time in the recent infrared investigation of Dehghany et al. [J. Chem. Phys. 130, 224310 (2009)]. As in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 11 publications
0
46
1
Order By: Relevance
“…Samples of each compound were prepared as a gas mixture of 0.04-0.08% difluoropyridine in neon and delivered to the pulsed nozzle with a backing pressure of 5-10 psi. These initial survey spectra guided our experiments using the more sensitive Balle-Flygare FTMW spectrometer [12] which was used to record individual hyperfine components with higher resolution ($7 kHz FWHM) and to seek lower intensity transitions. Gas mixtures for the FTMW measurements were more dilute (0.03%) and maintained at a higher backing pressure (80 psi) to optimize the signal.…”
Section: Methodsmentioning
confidence: 99%
“…Samples of each compound were prepared as a gas mixture of 0.04-0.08% difluoropyridine in neon and delivered to the pulsed nozzle with a backing pressure of 5-10 psi. These initial survey spectra guided our experiments using the more sensitive Balle-Flygare FTMW spectrometer [12] which was used to record individual hyperfine components with higher resolution ($7 kHz FWHM) and to seek lower intensity transitions. Gas mixtures for the FTMW measurements were more dilute (0.03%) and maintained at a higher backing pressure (80 psi) to optimize the signal.…”
Section: Methodsmentioning
confidence: 99%
“…1 It has been reported that one molecule of N 2 O has approximately 300 times the greenhouse warming potential of one molecule of CO 2 . The van der Waals (vdW) complexes of these "CO 2 family" molecules, especially their dimers [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and trimers, [18][19][20] have been the focus of both experiment and theory over the past few years. 2,3 Therefore, the N 2 O molecule and N 2 O-including complexes are of particular interest in the field of atmospheric chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Therefore, the N 2 O molecule and N 2 O-including complexes are of particular interest in the field of atmospheric chemistry. 16 Some interesting questions were raised, such as the relative stability of the isomers and the interconversion mechanism between these isomers. The wellknown "CO 2 family" of molecules consists of CO 2 , N 2 O and OCS, due to their isovalent electron number.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave spectrum of b-propiolactone was recorded using a Balle Flygare-type Fourier transform microwave (FTMW) spectrometer that has been described previously [11]. In comparison to older microwave techniques, linewidths on the order of 7 kHz can be achieved with FTMW spectroscopy and line positions are rou- tinely measured to an accuracy of ±1 kHz.…”
Section: Methodsmentioning
confidence: 99%